2015
DOI: 10.1016/j.mcn.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a inhibits K+ currents in hippocampal synapses through nitric oxide production

Abstract: Hippocampal synapses play a key role in memory and learning processes by inducing longterm potentiation and depression. The growth of adult synapses is regulated by the Wnt signaling pathway, in addition to other pathways. Wnt may also regulate the activity of the postsynaptic terminal. We have previously found that Wnt-5a induces nitric oxide (NO) production, which modulates NMDA expression in the postsynaptic regions of hippocampal neurons. Because the activity of Kv3.2 channels can be inhibited by NO, we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…This hypothesis is supported by the decrease in excitability by Li and VPA treatments in LR and NR neurons, respectively, and by the induction of hyperexcitability in control neurons by downregulation of LEF1. The relationship between Wnt signaling, neuronal excitability and synapse formation in the hippocampus has been observed previously [35,[91][92][93][94][95][96]. For example, WNT5A and WNT7A stimulate excitatory synapse formation in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 70%
“…This hypothesis is supported by the decrease in excitability by Li and VPA treatments in LR and NR neurons, respectively, and by the induction of hyperexcitability in control neurons by downregulation of LEF1. The relationship between Wnt signaling, neuronal excitability and synapse formation in the hippocampus has been observed previously [35,[91][92][93][94][95][96]. For example, WNT5A and WNT7A stimulate excitatory synapse formation in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, similar effects to those we have observed after chronic Wnt5a exposure have been reported as a consequence of an experimentally induced status epilepticus, in which a growing number of new neurons with an altered pattern in the location of their processes was found (Parent et al, ). Previous reports showed that Wnt activation through Wnt5 and Wnt3 modulates firing activity in the hippocampus (Oliva and Inestrosa, ), and increases the synaptic transmission and the number of the EPSPs in hippocampal slices (Parodi et al, ). Therefore, it is feasible to speculate that chronically infused Wnt5a might increase the basal hippocampal excitability, and also participates in the development of the abnormal pattern of neurite growth we found.…”
Section: Discussionmentioning
confidence: 99%
“…CAMKII activates a pathway that inhibits nuclear β-catenin, thereby inactivating Wnt/β-catenin transcriptional activity. The increase in cytosolic Ca 2+ has also recently been linked to production of nitric oxide (NO) in neurons, which influences synaptic excitability through modulation of potassium (K + ) channels [22]. …”
Section: Brief Overview Of Wnt Signalingmentioning
confidence: 99%
“…To modulate NMDAR synaptic transmission in hippocampal neurons, Wnt5a signals through receptor tyrosine-kinase-like orphan receptor 2 (Ror2) [217], a well-characterized Wnt receptor implicated in both Wnt/Ca 2+ and Wnt/PCP pathways [218,219]. This Wnt5a-Ror2-Ca 2+ -NO pathway also regulates hippocampal excitability by inhibiting voltage-gated K + currents (Kv currents) [22]. Kv channels play key roles in the spiking patterns of hippocampal neurons [220], and are thus important regulators of synaptic plasticity [221].…”
Section: Synapse Formation and Functionmentioning
confidence: 99%